Morphology and molecular characterization of the harmful dinoflagellate, protoceratium reticulatum (dinophyceae) - Liow, Guat Ru. (Universiti Malaysia Sarawak (UNIMAS), 2014)
Several species of the marine dinoflagellates are associated with harmful algae blooms (HABs), which have brought negative impacts to the coastal ecosystem of Malaysia and threaten lives. The species, Protoceratium reticulatum is one of the species that is capable of producing the toxic biocompounds, Yessotoxins (YTXs). In this study, the morphology of P. reticulatum found in Malaysian waters was characterized, and the genetics data assessed. In brief, field samplings were undertaken at Santubong estuary, Kuching, Sarawak. Clonal culture was established by single-cell isolation, and followed by species identification. Morphological characteristics of the cells were observed under scanning electron microscope (SEM) and epi-fluorescence microscope. Genomic DNA isolation was carried out for further molecular characterization. The nuclear encoded ribosomal RNA genes was amplified and sequenced. The sequences obtained were analyzed and phylogenetic relationship of the Malaysian strains of P. reticulatum were inferred by using maximum parsimony (MP), maximum likelihood (ML) and bayesian inference (BI). The results of the present study showed that the plate formula of Semariang strains with Po, 3', 1 a, 6", s, 6"', 2"". In contrast, the morphology characteristics of TalangTalang Island strain were failed to obtain due to failure in culture maintenance. The phylogenetic trees for both ITS and LSU sequences were constructed and showed Talang-Talang Island and Semariang strains formed two independent monophyletic clades. The phylogenetic tree revealed the grouping of closely related species. This study represents the first record of morphology and molecular characterization of Protoceratium reticulatumn from Malaysia.